(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics as well as endoscopic gastric–duodenal lesions, and to analyze the relationship between endoscopic findings, anemia status, and disease activity in patients with rheumatoid arthritis (RA) and anemia treated in Thai Nguyen. Subjects and Methods: A cross-sectional descriptive study was conducted on 39 patients with rheumatoid arthritis and anemia who underwent upper gastrointestinal endoscopy at the Department of Rheumatology, Thai Nguyen Central Hospital, and Thai Nguyen A Hospital from July 2024 to June 2025. Results: The mean age of patients was 61.87 ± 11.25 years. The disease duration of ≤ 2 years accounted for 59%. Most patients had mild anemia (89.7%). The mean number of painful and swollen joints was 10.64 ± 7.20 and 3.92 ± 3.32, respectively. The majority of patients (76.9%) had active or unstable disease activity. All patients presented with endoscopic lesions, with congestion/edema being the most common finding across all sites. Ulcerative lesions were most frequently observed in the duodenal bulb (31.2%), erosions were most common in the antrum (25%), and mucosal atrophy was most often found in the fundus (14.3%). There was a statistically significant association between ulcerative lesions and both the severity of anemia (p = 0.017) and disease activity level (p = 0.007). Conclusion: Patients with rheumatoid arthritis and anemia commonly exhibited unstable disease activity. Gastric–duodenal mucosal lesions on endoscopy were highly prevalent, and ulcerative lesions were significantly associated with both anemia severity and disease activity.